Exploring the relationship between community happiness and environmental setting / Siti Rasidah Md Sakip, Khalilah Hassan and Azran Mansor - Siti Rasidah, Md Sakip; Khalilah, Hassan; Azran, Mansor (2015)
This study argues that although scenic beauty, preference, and restoration are correlated due to their functional significance over evolution, they still can be distinguished from one another within natural landscapes. It is under category of environmental setting that correlate with quality of life among community. The sense of community and feeling secured living in neighborhood are another indicators as quality of life. A total of 86 respondents were randomly selected involving in this study. This study is quantitative in nature using a questionnaire. The survey involved asking residents to answer a questionnaire that was administered using face to face interviews. The questionnaire contained 6 parts:Part 1- background information, Part 2- the needs of public park, Part 3- perception of safety, Part 4 – fear of crime, Part 5- sense of community, and Part 6 - perception on crime prevention through environmental design (CPTED). Exploratory Factor Analysis (EFA) is used in the early stages to gather information about the interrelationships among variables. The Cronbach‟s Alpha (α) value was used to determine the level of reliability through the internal consistency for each factor. The result for validity of all construct achieved Alpha (α) value exceeding 0.70. The observation on environmental setting in neighborhood and district of Selama also carried out to identify environmental factors that contribute in quality of life among residents. Hence, the objective of this paper is to determine the factors that influence on Happiest Selama Community. Therefore at the end of this paper, the output will be used to find the relationship between environmental setting andfactors of quality of life among residents in Selama district.